PERILAKU POLITIK LEGISLATOR PEREMPUAN DALAM MEMPERJUANGKAN KEPENTINGAN PEREMPUAN - Rahmi Nuraini (Jurnal Ilmiah Komunikasi Makna, 2013)
Â AbstractThe lack of handling on issues related with woman as well as discriminative local regulations make womanâ€™s representativeness in politics becomes very important to influence the policy-making process becoming more sensitive towards issues on woman needs.This research, therefore, examines the political behaviors performed by legislative women in struggling for womanâ€™s interests, mainly the ones in the Provincial House of Representative of Central Java. Based on a basic assumption of â€œmuted group theoryâ€ by using a method of critical ethnographic analysis, it has been resulted that the struggle for womenâ€™s interests cognitively, affectively and behaviorally faces barriers coming from patriarchic cultural construction that humiliates women through verbal and non-verbal political language.The research finding shows that in terms of political language use, women apparently do not need to transform it into the menâ€™s accepted model (i.e. masculine model). Women can develop an alternative of communication model that combined masculine and feminine models to express experiences or codes in messages as a womenâ€™s way and to decrease the menâ€™s oppressions.Masculine model in womenâ€™s political language is done by adopting the values within masculine language, i.e. distinctive intonation, joke responding and sexual connotation. Meanwhile, feminine model is applied by changing the womenâ€™s weaknesses, which are regarded feminine, into a power verbally and non-verbally. Â AbstrakMasih kurangnya penanganan isu-isu yang berkenaan dengan perempuan serta peraturan daerah yang diskriminatif, membuat keterwakilan perempuan di bidang politik sangat penting demi terciptanya kebijakan yang lebih sensitif terhadap kebutuhan perempuan. Untuk itu, penelitian ini bermaksud mengkaji perilaku politik legislator perempuan dalam memperjuangkan kepentingan perempuan di Dewan Perwakilan Rakyat Daerah (DPRD) Provinsi Jawa Tengah.Dengan mendasarkan diri pada asumsi dasar â€muted group theoryâ€ dengan menggunakan metoda analisis etnografi kritis, dihasilkan bahwa perjuangan kepentingan perempuan baik secara kognisi, afeksi dan behavioralÂ  menemui hambatan yang berasal dari kontruksi budaya patriarki yang memberikan opresi melalui bahasa politik verbal dan nonverbal yang merendahkan perempuan. Hasil penelitian menunjukkan bahwa dalam bahasa politiknya, perempuan tidak harus mentransformasikan bahasa politik dalam model yang diterima oleh laki-laki (model maskulin). Perempuan dapat mengembangkan model alternatif untuk mengekspresikan pengalaman dan kode dalam pesan sebagai upaya mendefinisikan bahasa yang lebih dapat diterima. Model alternative yang menggabungan model maskulin dan feminine ini merupakan solusi terbaik legislator perempuan untuk mengurangi opresi yang dilakukan oleh laki-laki.Model maskulin dalam bahasa politik perempuan dilakukan mengadopsi nilai-nilai bahasa maskulin yaitu intonasi yang tegas, membalas guyonan dan konotasi seksual. Sementara model feminin dilakukan dengan mengubah kelemahan perempuan yang dianggap feminin menjadi kekuatan secara verbal dan nonverbal. Â